Evaluation of Surveyor nuclease for rapid identification of FKS genes mutations in Candida glabrata. Issue 6 (June 2021) - Khalifa, Hazim O.; Arai, Teppei; Majima, Hidetaka; Watanabe, Akira; Kamei, Katsuhiko
Abstract: Introduction: Infections with Candida glabrata have recently gained worldwide attention owing to its association with long hospitalizations and high mortality rates. This problem is highlighted when the infection is associated with echinocandin resistance, which is used for first-line therapy. Echinocandin resistance is exclusively attributed to functional mutations in FKS genes, and especially in hot spot (HS) regions. Unfortunately, few studies have focused on the rapid identification of FKS mutations associated with echinocandin resistance in C. glabrata . This study was intended to evaluate and validate the use of Surveyor nuclease assay (SN) for detection of FKS gene mutations. Methods: SN was evaluated against three segments of FKS1 and FKS2 genes including whole gene, regions including all HSs, and the region including only HS1. Results: Our results showed that SN results are basically dependent on the type of gene as well as the segment type. Interestingly, SN can detect mutations in the region containing HS1 in both FKS1 and FKS2 genes. Furthermore, SN can detect mutations in the segment containing all HS regions for FKS1 but not FKS2 . SN was unable to detect mutations in the whole FKS1 and FKS2 genes. Conclusions: As far as we know, this is the first study to validate SN for rapid identification of FKS gene mutations. This assay could be used as a sample for rapid identification of mutations associated with HS1 region in FKS genes, which have a predominant role for echinocandin resistance induction in C. glabrata.